O uso da audiodescrição como ferramenta no ensino de língua inglesa na escola pública - Silva, José Rildo Reis da (2024)
Translation in language teaching has several ideological barriers (Laviosa, 2014). However, the concept of translation goes far beyond just transposing written text from one language to another. Audiovisual Translation (TAV), for example, offers multiple possibilities for using translation in the classroom that go beyond the traditional exercise of translating sentences (Lertola, 2019). Based on the analysis of the production of Audio Description (AD) scripts for images in English language textbooks, this study sought to investigate the contribution of AD to the development of written production skills (writing) in the context of learning English through work in cooperative teams. The specific objectives were to verify how the production of AD texts contributes to the improvement of written production skills in English and to find out how cooperative tasks contribute to this development. As a methodology, this action research was carried out with 08 students without any visual impairment from the Centro Cearense de Idiomas (CCI) – Baturité Unit, who were studying module 4 of the basic English course at the time, corresponding to the transition between level A2 and B1 of the CEFR (2020) and who were also enrolled in high school in state public schools in the region. The students participated in a mini-course in which audio description tasks were used combined with the content presented in the Moderna Plus textbook (Almeida, 2020). As an evaluation method to compose the database for analysis, they responded to a survey questionnaire, a pretest, a post-test, in addition to an evaluation of the mini-course. The mini-course had recorded classes, covering 18 hours, divided into 6 3-hour meetings, which were conducted in person at the CCI headquarters. The result of the pre-test and post-test analysis, as well as the classroom observations and the general evaluation of the course, demonstrated that the participants were able to structure the texts better after the intervention, adding more details to the textual productions through the use of more I need vocabulary, such as locative expressions and adjectives. It was also possible to notice a slight increase in linguistic proficiency, with an emphasis on the cohesive articulation of the text. Participants also demonstrated satisfaction in working in cooperative groups, as they were able to exchange ideas, ask questions and discuss the images during the course. As a limitation, the study could have been carried out with a larger number of students and over a longer class period. As a gap for future studies, it is suggested that researchers address other linguistic skills, such as listening and oral production.